Queen's Park Savannah. Trinidad. B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Here is an old photograph of the Queen’s Park Savannah, circa 1930. A man is standing near his grazing animals. One of the first uses of the Savannah was for public pasture. After emancipation, the public was given permission to graze cattle on the land. In the mid-ground of this photograph on the left is a building that was once the residence of the Governor of Trinidad and Tobago, now President's House. On the right are a number of trees and palms and in the background is a section of the Northern Range.
Colour: Black and White; Style: Landscape; Other: Unbordered; Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Palms--Trinidad and Tobago; Mountains--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Horse racing--Trinidad and Tobago; Cattle--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)